Effect of wettability on hydrodynamics and mass transfer in small capillaries - Sampat, Chaitanya; Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2021)
The wettability of the reactor wall has a significant effect on the interfacial liquid?liquid mass transfer rates in segmented flow. This work quantitatively demonstrates the importance of choosing the right material of construction of flow reactors to achieve the desired mass transfer performance. Glass and PTFE capillaries of identical diameter were used to study the effect of hydrophilic and hydrophobic surfaces on the hydrodynamics and mass transfer of the system. It was observed that for the overall mass transfer coefficient (kLa) changed by two orders of magnitude depending on the wettability of the continuous phase. The observations indicated that it is essential to achieve complete wetting of the capillary walls by the continuous phase for significant mass transfer enhancement. The observations are discussed on the basis of film thickness and slip velocity at the wall as well as the slip velocity at liquid?liquid interface. Predictions of the mass transfer coefficient using a model based on the interfacial and fluid properties showed excellent match with the experiments thereby allowing us to explore the effects of wettability on the overall mass transfer coefficient in greater detail. ? 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Liquid?liquid slug flow; Mass transfer; Slip velocity; Wettability